Lyophilised reconstituted human platelets increase thrombus formation in a clinical ex vivo model of deep arterial injury - Joshi, Nikhil Vilas; Raftis, Jennifer B.; Lucking, Andrew J.; Hunter, Amanda H.; Millar, Mike; Fitzpatrick, Mike; Feuerstein, Giora Z.; Newby, David E. (Thrombosis and Haemostasis, 2012)
Platelets are the principal component of the innate haemostatic system that protect from traumatic bleeding. We investigated whether lyophilised human platelets (LHPs) could enhance clot formation within platelet-free and whole blood environments using an ex vivo model of deep arterial injury. Lyophilised human platelets were produced from stored human platelets and characterised using conventional, fluorescent and electron microscopic techniques. LHPs were resuspended in platelet-free plasma (PFP) obtained from citrated whole human blood to form final concentrations of 0,20 and 200 × 109 LHPs/L. LHPs with recalcified PFP or whole blood were perfused through the chamber at low (212 s-1) and high (1,690 s-1) shear rates with porcine aortic tunica media as thrombogenic substrate. LHPs shared morphological characteristics with native human platelets and were incorporated into clot generated from PFP or whole blood. Histomorphometrically measured mean thrombus area increased in a dose-dependent manner following the addition of LHPs to PFP under conditions of high shear [704 μm2 ± 186 μm2 (mean ± SEM), 1,511 μm2 ± 320 μm2 and 2,378 μm2 ± 315 μm2, for LHPs at 0, 20 and 200 × 109 /l, respectively (p= 0.012)]. Lyophil-ised human platelets retain haemostatic properties when reconstituted in both PFP and whole blood, and enhance thrombus formation in a model of deep arterial injury. These data suggest that LHPs have the potential to serve as a therapeutic intervention during haemorrhage under circumstances of trauma, and platelet depletion or dysfunction.
Keywords: Bleeding disorders; haemostasis; lyophilised human platelets; platelet substitutes